Κ-Carrageenan from marine red algae, Kappaphycus alvarezii – A functional food to prevent colon carcinogenesis. (May 2015) - Raman, Maya; Doble, Mukesh
Highlights: Sulphated galactans from red marine algae, Kappaphycus alvarezii induced apoptotic cell death in HCT116. It downregulated the expression of XIAP and PARP-1. It upregulated the ROS levels and the expression of caspase3 in HCT116. Abstract: Both the insoluble and soluble fibres have health benefits and could be used as food additive and in pharmaceutical and other industries. In the current study, the role of soluble dietary fibre fractions of marine red algae, Kappaphycus alvarezii (κ-carrageenan) against human colon cancer cells, was investigated. It comprises of D-galactose and 3, 6-anhydro-D-galactose, linearly linked by α(1→3) and β(1→4) glycosidic linkages. Exposure of human colon cancer cells, HCT116, to the sulphated fractions (F1 and F2) resulted in apoptotic cell death, nuclear fragmentation, apoptosome formation, upregulation of the mRNA expression levels of Bcl-2, Bcl-xL and caspase3 and the downregulation of XIAP and PARP-1. The treatment also enhanced the intracellular mitochondrial ROS levels in HCT-116 but not in HEK293 and L6. The apoptosis in HCT116 is possibly induced through the ROS-mediated mitochondrial pathway combined with downregulation of XIAP and upregulation of caspase3. The former induces DNA damage leading to G1 cell cycle arrest and apoptosis. Low cytotoxicity and anticarcinogenic effects of the soluble dietary fibre fractions from K. alvarezii on HCT116 suggests an alternative approach to metastatic human colon cancer therapy and highlights the importance of marine dietary fibre as a food supplement.